Nanocrystalline Ag3PO4 for sunlight- and ambient air-driven oxidation of amines: high photocatalytic efficiency and a facile catalyst regeneration strategy - Garg, Reeya; Mondal, Sanjit; Sahoo, Lipipuspa; Vinod, C. P.; Gautam, Ujjal K. (ACS Applied Materials & Interfaces, 2020)
Selective oxidation of amines to imines using sunlight as clean and renewable energy source is an important but challenging chemical transformation because of high reactivity of the generated imines and lack of visible light-responsive materials with high conversion rates. In addition, oxygen gas has to be purged in the reaction mixture in order to increase the reaction efficiency which, in itself, is an energy-consuming process. Herein, we report, for the first time, the use of Ag3PO4 as an excellent photocatalyst for the oxidative coupling of benzyl amines induced by ambient air in the absence of any external source of molecular oxygen at room temperature. The conversion efficiency for the selective oxidation of benzyl amine was found to be greater than 95% with a selectivity of >99% after 40 min of light irradiation indicating an exceptionally high conversion efficiency with a rate constant of 0.002 min(-1), a turnover frequency of 57 h(-1), and a quantum yield of 19%, considering all of the absorbed photons. Ag3PO4, however, is known for its poor photostability owing to a positive conduction band position and a favorable reduction potential to metallic silver. Therefore, we further employed a simple catalyst regeneration strategy and showed that the catalyst can be recycled with negligible loss of activity and selectivity.
Keywords: amine oxidation; energy harvesting; nanocrystalline Ag3PO4; Photocatalysis; regeneration strategy

Wavelength dependent luminescence decay kinetics in `quantum-confined' g-C(3)N(4)nanosheets exhibiting high photocatalytic efficiency upon plasmonic coupling - Mondal, Sanjit; Sahoo, Lipipuspa; Vaishnav, Yuvraj; Mishra, Samita; Roy, Raj Sekhar; Vinod, C. P.; De, Arijit K.; Gautam, Ujjal K. (Journal of Materials Chemistry A, 2020)
Serendipitous observations offer newer insights into materials properties. Here we describe g-C(3)N(4)nanosheets exhibiting remarkably blue-shifted photoluminescence within the 390-580 nm range centred at 425 nm which matches more closely with its `quantum-dots', and yet is excitation-wavelength independent. Moreover, surprisingly, the luminescence decay becomes increasingly slow at higher emission wavelengths, by up to 10 times. The nanosheets absorb only a fraction of visible-light. To improve this, when we designed a nanocomposite of g-C(3)N(4)and Au nanoparticles (NPs), it retained the PL characteristics and also exhibited excellent light-harvesting and photocatalytic efficiency for benzylamine (BA) oxidation. The surface plasmon resonance of the Au NPs is responsible for the high visible-light response and assisting the reaction by the `hot-electron' injection mechanism, while an uncharacteristic, pronounced co-catalytic effect by them further improves the efficiency. The conversion is 98% with >99% selectivity over 1.5 h of natural sunlight and open-air, probably the highest efficiency for BA photo-oxidation reactions. Even though such a dual role by plasmonic NPs has remained unscrutinized, we argue that the charge-transfer processes for the `hot-carrier' injection and co-catalytic events are well-separated in time due to a much slower photon incident frequency on a catalyst particle, enabling both to occur simultaneously in the same particle.

Autophagy and unique aerial oxygen harvesting properties exhibited by highly photocatalytic carbon quantum dots - Mondal, Sanjit; Vinod, C. P.; Gautam, Ujjal K. (Carbon, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Plastic pollution is a serious threat to the environment as they are not bio-degradable. Herein using waste-polyethylene, we report two inter-related important findings. First that they can be converted economically and completely into highly photocatalytic carbon quantum-dots (CQDs) using H<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> as a residue-free oxidant in an acid medium, and they have the ability to enrich a reaction medium with an extraordinary amount of molecular oxygen harvested from the air so that no separate oxygen source is needed while carrying out facile photocatalytic <a class="topic-link" href="https://www.sciencedirect.com/topics/engineering/oxidation-reaction" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about oxidation reactions from ScienceDirect's AI-generated Topic Pages">oxidation reactions. Second, when they are not performing any photocatalytic reaction, they exhibit self-sensitized photo-oxidation to convert themselves completely to CO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> in the presence of sunlight, a phenomenon that we term as ‘CQD-autophagy’ by drawing parallels to the death of useless-cells in the body. Such extinction from the reaction media is unique as no other material is known to do so and advantageous because the removal of carbon-dots from a solution is rather inefficient from an industry-viewpoint due to their high solubility. Instead, the inexpensive CQDs can be discarded casually with the notion that they will gradually get eliminated from the environment.
Keywords: Carbon dots; Oxygen-enrichment; Photocatalytic oxidation; Self-sensitized photo-oxidation

Facile transfer of excited electrons in Au/SnS2 nanosheets for efficient solar-driven selective organic transformations - Mondal, Sanjit; Sahoo, Lipipuspa; Vinod, C. P.; Gautam, Ujjal K. (Applied Catalysis B-Environmental, 2021)
Solar driven aerial oxidation processes have gained importance in organic transformations leading to the development of many nanocrystalline photocatalysts. Although such nanomaterials have many potential advantages, they often underperform due to poor visible light absorption and rapid recombination of excitons. Incorporation of plasmonic nanoparticles (NPs) on the catalyst surfaces can extend their response to visible light and improve photocatalytic efficiency by the `hot-electron' injection mechanism. Nanostructures of SnS2 too absorb a part of the visible light to induce many photocatalytic reactions, though their ability to perform the selective and controlled organic transformations has not yet been observed. Herein, we demonstrate the first example of such transformation with the oxidative coupling of various benzylamine (BA) derivatives to imines under ambient conditions using SnS2 nanosheets (NSs). The reaction rate improves manifold and shows similar to 98 % conversion (>99 % selectivity) in 2 h under direct sunlight and open-air when the NSs were decorated with 1.5 wt% Au NPs on (Au/SnS2), making it one of the best catalysts for this reaction. We found that the large enhancement in activity upon Au loading is accompanied by a noticeable change in photo-induced charge accumulation behaviour in Au/SnS2 from the usual ``spike and overshoot'' one and contributed by facile transfer of excited electrons across the Au-SnS2 heterojunction in which Au NPs act as both sources and sinks for the photo-excited electrons. Finally, a detailed mechanism of the oxidation reaction has been proposed.
Keywords: Benzylamine oxidation; Hot-electron injection; Plasmonic nanoparticle; SnS2 nanosheet; Solar energy harvesting

Influence of support textural property on CO2 to methane activity of Ni/ SiO2 catalysts - Cherevotan, Arjun; Ray, Bitan; Churipard, Sathyapal R.; Kaur, Komalpreet; Gautam, Ujjal K.; Vinod, Chathakudath P.; Peter, Sebastian C. (Applied Catalysis B-Environmental, 2022)
In this work, we elucidated the role of physicochemical textural properties of inert support on the catalyst ac-tivity by impregnating Ni on ordered mesoporous silica (SBA-15 and MCM-41) and non-mesoporous silica (nMPS). The catalyst Ni/SBA-15 exhibited the best CO2 conversion (83%) and product selectivity (99.9 %) followed by Ni/MCM-41 and the least by Ni/nMPS. The difference in the nature of the catalyst, degree of nanoparticle distribution and nanoparticle encapsulation by different silica support were studied by N2 adsorption-desorption and X-ray photoelectron spectroscopy (XPS) experiments. The Operando Diffused Reflec-tance Infrared Fourier Transform Spectroscopy were used to understand the variance in reaction pathway which is accredited to the textural properties of the support. The SBA-15 supported Ni catalyst followed dissociative CO pathway while MCM-41 and nMPS reacted through associative formate mechanism as major pathway. These findings provide a novel perspective on CO2 hydrogenation over Ni-silica, allowing us to tune both activity and selectivity.
Keywords: CO2 methanation; DRIFTS; Mesoporous silica support; Textural properties

`Self-activating' Bi3TaO7-Bi4TaO8Br photocatalyst and its use in the sustainable production of pro-fluorophoric rhodamine-110 - Banoo, Maqsuma; Chatterjee, Kaustav; Mondal, Sanjit; Vinod, C. P.; Gautam, Ujjal K. (Green Chemistry, 2022)
We counter two common notions that (i) photocatalysts are likely to degrade during use with barely any strategy to counter it and (ii) rhodamine-B (RhB) photo-degradation lacks any useful or commercial prospects even after 53 years of its discovery by developing a photocatalyst that continues to improve its activity for similar to 300 h due to a leaching induced `self-activation' process. Rhodamine-110 (Rh110) is a widely used pro-fluorophore in biological studies. However, its commercial production is highly challenging due to the formation of various side-products originating from the presence of the two labile amino side-groups that induce the pro-fluorophore activity, leading to purification difficulties, low yield, and unusually high costs. Herein, we demonstrate a facile strategy to produce pure Rh110 using extremely inexpensive RhB and Bi3TaO7-Bi4TaO8Br heterostructures as a catalyst in sunlight. The catalyst is not just stable over 30 catalytic cycles but also gets activated continuously in successive cycles to produce a reaction yield as high as 88%. The role of the heterostructure, the origin of surface activation, and the RhB -> Rh110 transformation mechanism have been established. Based on 150 days of sunlight experiments, large-scale production prospects (similar to 4000 times scale-up) and isolation of Rh110 have also been realized, paving a novel way for its production by anyone, inexpensive biological essaying, and device fabrication. Continuously improving catalysts are unknown and compensatory leaching of metal atoms from the catalyst surface may pave the way to realize them.

Single-step insertion of M-Nx moieties in commercial carbon for sustainable bifunctional electrocatalysis: mapping insertion capacity, mass loss, and carbon reconstruction - Garg, Reeya; Sahoo, Lipipuspa; Kaur, Komalpreet; Vinod, C. P.; Gautam, Ujjal K. (Carbon, 2022)
Atomically dispersed earth-abundant metals in N-doped carbon (M-N-Cs) have emerged as a new class of electroactive materials that can match not only the performance of the precious metals but can catalyze both the cathodic and the anodic reactions due to their bifunctional behaviour. This inspires the development of simpler strategies for scale-up production since the existing ones rely on precursors whose commercial viability is not yet ascertained. Herein, we demonstrate the insertion prospects of M-Nx (M = Fe, Co, Ni) moieties, the electrocatalytic centers in the M-N-Cs, into commercial carbon to establish that a single-step heating of the inexpensive precursors is sufficient to generate bifunctional electrocatalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) with efficiencies that bypass the majority of the known catalysts. Further importantly, we quantify both the ORR and OER trends and the metal insertion limits for each metal while maintaining an atomic dispersion, without the formation of surface migration-induced clustering, because such clustering is inevitable in the existing processes to necessitate an extra acid-leaching step to remove them. We further quantify and explain for each metal a negative mass balance originating from anomalous mass loss of both metal and carbon content, and a massive reconstruction of the carbon backbone catalyzed by the very metal, an event documented for the first time though it ought to be associated with other M-N-C syntheses too. The study establishes an incredibly simple and inexpensive strategy for the realization of M-N-Cs and outlines the parameters to be considered during mass-production.
Keywords: Bifunctional catalysis; Carbon reconstruction; Commercial carbon; Metal insertion; Oxygen electrocatalysis

Tuning the hybridization and charge polarization in metal nanoparticles dispersed over Schiff base functionalized SBA-15 enhances CO2 capture and conversion to formic acid - Cherevotan, Arjun; Ray, Bitan; Yadav, Anish; Bagchi, Debabrata; Singh, Ashutosh Kumar; Riyaz, Mohd; Churipard, Sathyapal R.; Naral, Vinay; Kaur, Komalpreet; Gautam, Ujjal K.; Vinod, Chathakudath P.; Peter, Sebastian C. (Journal of Materials Chemistry A, 2022)
Different Schiff base functionalized SBA-15 materials were synthesized through condensation reactions between 3-aminopropyltriethoxysilane (APTES) and different aldehydes (glutaraldehyde and butyraldehyde) over a mesoporous silica, SBA-15 (APTES-GLU/SBA-15 and APTES-BUT/SBA-15). Both static and dynamic experiments have been used for testing the CO2 capture efficiency of these materials. The hybridization of the N atom in APTES has been tuned from sp(3) to sp(2) upon condensation facilitating optimum CO2 capture in the direct synthesis of APTES-GLU/SBA-15. The undesirable oxides of nitrogen have been removed during the synthesis process to improve the CO2 capture efficiency. These materials were employed as supports for Pd-Ag and Pd-Ni bimetallic systems for the selective conversion of the captured CO2 to formic acid (FA) in 0.5 M KHCO3 solution. The Pd-Ni catalyst system exhibited enhanced CO2 to FA conversion activity compared to other heterogeneous systems, which is similar to 4 times better than that of the Pd-Ag system in this study. The X-ray absorption studies over the catalyst material confirmed that the relatively electron-deficient Ni in Pd-Ni compared to Ag in Pd-Ag favoured higher charge polarization between the metals in the Pd-Ni system enhancing the CO2 to FA conversion. The experimental observations are well supported by the DFT calculations.

Ultrathin twisty PdNi alloy nanowires as highly active ORR electrocatalysts exhibiting morphology-induced durability over 200 K cycles - Sahoo, Lipipuspa; Garg, Reeya; Kaur, Komalpreet; Vinod, C. P.; Gautam, Ujjal K. (Nano Letters, 2022)
Even though the anion exchange membrane fuel cells have many advantages, the stability of their electrocatalysts for oxygen reduction reaction (ORR) has remained remarkably poor. We report here on the ultrathin twisty PdNi-alloy nanowires (NWs) exhibiting a very low reaction overpotential with an E1/2 ∼ 0.95 V versus RHE in alkaline media maintained over 200 K cycles, the highest ever recorded for an electrocatalyst. The mass activity of the used NWs is >10 times higher than fresh commercial Pt/C. Therein, Ni improves the Pd d-band center for a more efficient ORR, and its leaching continuously regenerates the surface active sites. The twisty nanowire morphology imparts multiple anchor points on the electrode surface to arrest their detachment or coalescence and extra stability from self-entanglement. The significance of the NW morphology was further confirmed from the high-temperature durability studies. The study demonstrates that tailoring the number of contact points to the electrode-surface may help realize commercial-grade stability in the highly active electrocatalysts.

Covalently interconnected layers in g-C3N4: toward high mechanical stability, catalytic efficiency and sustainability - Roy, Raj Sekhar; Mondal, Sanjit; Mishra, Samita; Banoo, Maqsuma; Sahoo, Lipipuspa; Kumar, Amit; Vinod, C. P.; De, Arijit K.; Gautam, Ujjal K. (Applied Catalysis B: Environmental, 2023)
The grim prospects for the industrial utilization of g-C3N4 nanosheets arise from multi-step processing resulting in low material yields and poor visible light response due to quantum confinement. Herein, we introduce a strategy for linking the adjacent layers of g-C3N4 covalently to realize a high surface area without excess mass loss in a one-step process by introducing diethylene glycol as a precursor that produces-(CH2)2-O-(CH2)2-linkers in-situ. Their presence increases interlayer spacing and introduces surface curvatures, discouraging the stacking of a larger number of layers to produce nanosheets with-3 times higher surface area. Interestingly, unlike other layered materials, the linkers also provide extraordinary mechanical stability against exfoliating forces. In addition, the process instills sub-bandgap states and a considerable visible light response at 500 nm to slow down the picosecond exciton recombination dynamics, resulting in-5 times enhancement in H2 generation efficiency from photocatalytic water-splitting over the bulk sample.
Keywords: Layer-linkers; Sustainable synthesis; Transient absorption spectroscopy; water-splitting